Electronic Fund Transfer: A Mechanism To Money Laundering Crime (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Many new developments in the field of information  technology have affected modern society in numerous  ways, including advancement in communication, education, commerce, and so on. These modern up  gradations have brought incredible benefits to the society  at large but they have also provided numerous  opportunities for various forms of crime, thus making crime  a highly profitable avenue. Among the many types of  criminal activities, modern technology has allowed money  laundering to become an online crime. Money laundering  is the process where cash raised from criminal activities is  made to look legitimate for re-integration into the financial  system. It also refers to the process of concealing the  source of money obtained by illicit means. This new type of  crime has raised some legal questions about the capability  of national and international regulations in relation to  current and upcoming issues. These include finding  electronic funds transfer records and determining money  laundering activity that includes electronic funds transfer. Electronic funds transfer (EFT) is the electronic  exchange, transfer of money from one account to another,  either within a single financial institution or across multiple  institutions, through computer-based systems. Electronic  money provides an easy method of transferring value  without revealing identity. The increase in the amount of  crime indicates the following series of techniques and  mechanisms that had been detected in relation to money  laundering activity. This research will examine current  issues under the light of various regulations, and will put  forward some proposals to close the legal vacuum.
Keywords: Electronic Fund Transfer; Money Laundering; Technology and Crime Interaction; Developing Economy